2022
DOI: 10.1038/s41598-021-04366-6
|View full text |Cite
|
Sign up to set email alerts
|

Annual change in the extracellular fluid/intracellular fluid ratio and mortality in patients undergoing maintenance hemodialysis

Abstract: We aimed to investigate whether annual change in the extracellular fluid to intracellular fluid (ΔECF/ICF) ratio can accurately predict mortality in hemodialysis patients. Totally, 247 hemodialysis patients were divided into two groups according to the median baseline ECF/ICF ratio of 0.563 and ΔECF/ICF ≥ 0% or < 0% during the first year, respectively. Thereafter, they were divided into four groups according to each cutoff point and were followed up for mortality assessment. The ECF/ICF ratio increased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…PEW, a malnutritional state defined by a loss of fat and muscle mass because of catabolic inflammation, is prevalent in patients receiving HD and is also related to increased risks of mortality [4,[21][22][23][24]. The MIS proposed by Kalanter-Zadeh et al is the gold standard method for assessing the nutritional status of HD patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…PEW, a malnutritional state defined by a loss of fat and muscle mass because of catabolic inflammation, is prevalent in patients receiving HD and is also related to increased risks of mortality [4,[21][22][23][24]. The MIS proposed by Kalanter-Zadeh et al is the gold standard method for assessing the nutritional status of HD patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…Given the suggested association of ECW/TBW ratio with proteinenergy wasting and the elevated mortality risk linked to a ratio surpassing 0.4 [13], our study delved into assessing this ratio within the study cohort. Induction of tirzepatide did not affect the ECW/TBW ratio (0.40 ± 0.01 vs. 0.40 ± 0.01; p = 0.172, Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in DW because of tirzepatide treatment was −3.5 ± 0.5 kg and was also observed over an extended period of time; however, the effect was observed mainly in body fat content, showing no discernible impact on skeletal muscle mass and SMI. Recent studies have demonstrated that a decrease in SMI, or the appearance of sarcopenia and frailty, is often observed in patients with CKD, which shortens their life expectancy [13]. In this regard, tirzepatide only reduces fat and does not affect muscle mass, thereby eliminating concerns regarding sarcopenia and frailty in patients with DKD undergoing HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the BIA-measured ratio of extracellular water (ECW) to intracellular water (ICW), which can simultaneously reflect fluid overload and malnutrition, has emerged as an indicator of PEW in patients receiving hemodialysis [24]. The ECW/ICW ratio can help predict cardiovascular mortality, cardiovascular events, and all-cause mortality in this population [24][25][26]. Park et al reported that ECW fluid overload was associated with sarcopenia in the general population [27].…”
Section: Introductionmentioning
confidence: 99%